Adolescents Discussing Sexual Behaviors With Key Influencing Audiences - Nalukwago, Judith; Crutzen, Rik; Bart, van den Borne; Bukuluki, Paul M.; Bufumbo, Leonard; Batamwita, Richard; Zikusooka, Amos; Thompson, Gretchen; Alaii, Jane (Global Journal of Health Science, 2018)
There is an increasing concern on early initiation of sexual activity among adolescents, increasing sexually transmitted infections, and teenage pregnancy in Uganda. Adolescents perceptions of these sexual behaviors might be the result of discussing sexual and reproductive health issues with key influencing audiences. This study qualitatively explored the effect of sexuality discussions with key influencing audiences by means of in-depth interviews and focus group discussions with adolescents (N=83). Findings indicate that adolescence stage comes with changes of intense sexual desires, often presumed difficult to control thus leading adolescents to engage in sexual activities. Adolescents indicated that they were aware of the sexual behaviors such as condom use, contraception use, and multiple concurrent partnerships, but intertwined with persistent myths and misconceptions. Although discussing sexuality issues with someone was found to be instrumental, adolescent highlighted challenges that hinder discussion with key influencers. Challenges include, parents lack of time to talk to their children; some religious affiliations perceived to discourage use of contraception; limited skills of community health workers to address adolescent information needs; meetings held in groups not followed up with age-focused or one-on-one discussions; negative health workers’ attitudes and use of technical language; and peer pressure. These findings suggest the need to provide adequate and updated information to clear any misconceptions and strengthening of key influencers’ communication skills to gain confidence in addressing adolescent sexual and reproductive health needs.
Keywords: Adolescents; Condom use; Contraception; Multiple concurrent partnerships; Key influencers